Impact of Climate Change on Sugarcane Productivity in the Southern Part of Nepal Using DSSAT-CANEGRO Model - Jha, Mukti Nath; Chaudhary, Ravi Prasad; Alam, Jawed; Rai, Yam Kumar; Joshi, Manoj Kumar; Adhikari, Jagat Bandhu; Khadka, Sujan; Mishra, Anjay Kumar (Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2024)
The research on impact of climate change in variety specific sugarcane cultivation in southern part of Nepal revealed realistic assessment on forecasting impact of climate change in sugarcane production as well as their successful adaptation strategic for agricultural management and future planning. The objective of this research is to describe climatic sensitivities of sugarcane; assessment on their yield simulation using DSSAT-CANEGRO model of five distinct sugarcane varieties that was cultivated in NSRP; and to calibrate and validate the simulated & observed and adaptation strategic for early, mid and late cultivars; and. The model created four years distinct simulated yields in which datasets was calibrated for consecutive two fiscal years (2018-19 and 2019-20) and validated with consecutive two fiscal years’ (2020-21 and 2021-22). The sugarcane varieties (Co 86032, Co 0118, BO 120, CoSe 98255, CoS 08272) showed correlation coefficient of 0.5983, 0.889, 0.8713, and 0.7591. The sensitivity analysis on yield has been simulated with wide range of weather parameters with its values in two stage of sugarcane crop: germination and growth development. The climate modification has been done with DSSAT model as individual as well as combined form with weather parameters Tmin (±1 to ±3˚C), Tmax (±1 to ±3˚C), solar radiation Tmax (±1 to ±3 MJ/m2/day), and default CO2 concentration of 380 ppm to 500 ppm and 720 ppm scenario. The studied disclosed that with decrease in weather parameters value; the simulation yield of sugarcane decreases with decrease in parameters value and with increase in Tmax, Tmin, Solar radiation; the simulated yield increases but very slight effect of CO2 increase in yield except Co-86032 & CoSe-98255 in both stages.